Pemamfaatan Aplikasi Googleform Dalam Pembelajaran Bagi Guru Pada Masa Pandemi - Yanthi Charolina; Honny Honny (Paradigma, 2021)
The Google meet application and Google form are being studied and used by many teachers and students during the current pandemic. At this time all countries in the world are experiencing a crisis along with the entry of the Corona / Covit'19 virus which has killed many victims, even though many are still being treated with special handling in hospitals. The whole world is struggling to eradicate the virus that is currently developing. With this virus, countries around the world apply to stay at home to avoid crowds so that they can suppress this virus from developing. Many countries have locked down the place in order to suppress the development of this virus. Indonesia is one of the countries that also implements LockDown but in other terms, namely, PSBB means Large-Scale Social Restrictions. Where the Government recommends that all activities be carried out at home, one of which is in the field of education, namely school, where students can only receive learning from home and teachers also from home. This is where the use of information and communication technology is needed in carrying out teaching and learning activities. Currently, all teachers in schools must be able to take advantage of advanced information and communication technology to teach their students.The purpose of this study is to obtain an overview of the extent to which teachers in schools use or utilize information and communication technology that is currently developing using the internet in teaching and learning activities. In this study, research focuses on understanding social phenomena that occur in society.